Sosialisasi Membangun Kesadaran dan Pengetahuan Masyarakat Tentang Zakat Fitrah Di Kelurahan Bulit Jengkol Kecamatan Pangkalan Susu - Usmaidar; Novira Arafah; Risko Khoir Nasution; Mardiana; Dina Oktavia Waode; Rio Ferbryan (peduli riset dan pengabdian masyarakat, 2023)
Zakat is one of the financial and socio-economic institutions in Islam that has the potential to reduce poverty and improve people's economic welfare. Zakat as one of the pillars of Islam has animportant role in all eviating theeconomicburdenonMuslims in need. However, there are stillmanypeoplewhodo not understandwellabout zakat and its benefits for zakat recipients and zakat givers. Therefore, the socialization of zakat is very important to increase people's understanding of zakat. Zakat recipients, according to the definition of Islamic teachings, include the poor, needy, debt-ridden, travelers, and others who are deemed eligible to receive assistance. Zakat is usually channeled through established channels, such as mosques, charitable organizations, and designated individuals, to ensure that it reaches those in need in an effective and efficient manner. Zakat is not only a means of providing for those who are less fortunate, but also functions as a means of purifying wealth, cleansing the soul, and fostering a sense of empathy and social solidarity among Muslims. It is usually calculated based on a certain proportion of a person’s wealth, usually ranging from 2.5% to 10%, depending on the type of asset and amount owned. Zakat is considered a religious obligation in Islam and has an important meaning in the lives of devout Muslims. It is an act of worship that promotes compassion, generosity, and social welfare, and plays an important role in supporting those in need and building a more just society according to Islamic teachings.